Age-Dependent Pre-Vaccination Immunity Affects the Immunogenicity of Varicella Zoster Vaccination in Middle-aged Adults - van der Heiden, Marieke; de Rond, Lia G. H.; van Zelm, Menno C.; Berbers, Guy A. M.; Boots, Annemieke M. H.; Buisman, Anne-Marie (Frontiers in Immunology, 2018)
Background Prevention of infectious diseases is of high priority in the rapidly ageing population. Unfortunately, vaccine responses in the elderly are frequently diminished. Timely vaccination of middle-aged adults might improve the immune responses to vaccines, although knowledge on pathogen-specific immune responses and factors affecting these responses, in middle-aged adults is currently limited. We thus investigated the immune responses after vaccination with Zostavax consisting of live attenuated varicella zoster virus (VZV). Methods Blood samples were taken pre-, 14 days, 28 days, and 1 year after a primary VZV vaccination (Zostavax) at middle-age (N=53, 50-65 years of age). VZV-specific IFNγ-producing cells were measured by Elispot, activated T-cells by flow cytometry, antibody levels and cytokine responses by fluorescent bead-based multiplex immunoassays, and whole blood cellular kinetics by TruCOUNT analysis. Results Robust short-term enhancement of the VZV-specific IFNγ producing cell numbers was observed post-vaccination in the middle-aged adults. Remarkably, long-term enhancement of VZV-specific IFNγ producing cell numbers was induced only in participants with low numbers of VZV-specific pre-vaccination IFNγ producing cells, who were significantly older. These participants also showed enhancement of VZV-specific activated CD4 T-cells, contrary to ‘exhausted’ VZV-specific CD8 T-cells in participants with high numbers of VZV-specific pre-vaccination IFNγ producing cells. Finally, a high CD4/CD8 T-cell ratio was associated with low numbers of pre-vaccination VZV-specific IFNy producing cells . Conclusion These results suggest that adults in their early sixties, who showed a high CD4/CD8 T-cell ratio and low numbers of VZV-specific IFNγ producing cells, benefit from VZV vaccination. This provides important knowledge on factors affecting VZV-specific immune responses in middle-aged adults as well as for strategies to strengthen immunity before reaching old age.